Conversation with Ted Jackson, Carleton University (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2017)
In the Exchanges, we present conversations with scholars and practitioners of community engagement, responses to previously published material, and other reflections on various aspects of community-engaged scholarship meant to provoke further dialogue and discussion. We invite our readers to offer in this section their own thoughts and ideas on the meanings and understandings of engaged scholarship, as practiced in local or faraway communities, diverse cultural settings, and various disciplinary contexts. We especially welcome community-based scholars’ views and opinions on their collaboration with university-based partners in particular and on engaged scholarship in general. Natalia Khanenko-Friesen talks to Edward “Ted” Jackson about his work and his views on engaged scholarship in Canada. Dr. Jackson is a senior research fellow of Carleton Centre for Community Innovation and adjunct research professor in Public Policy and Administration, International Affairs and African Studies at Carleton University, Ottawa. Ted Jackson served as a the conference convenor for C2UExpo, held at the Carleton in May 2015.